2010
DOI: 10.1080/02635140903513573
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of peer instruction and structured inquiry on conceptual understanding of force and motion: a case study from Thailand

Abstract: This study proposed to investigate the effectiveness of learning activities based on a conceptual change theoretical framework by embedding a peer instruction method with structured inquiry (PISI) on tenth grade students' understanding of force and motion concepts. This teaching method was compared to the existing traditional instruction (TI). Alternative conceptions of force and motion were determined through related literature and a preliminary study, carried out prior to instruction, was used for designing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 29 publications
1
7
0
4
Order By: Relevance
“…The percentage increase (Δ = <s post > -<s pre >) in the Mechanics test is equal to 32.20%, with a more pronounced effect on female's value (44.19%) than male's findings (27.60%), and even bigger in Electromagnetism, which is equal to 55.48% (49.28% for female's findings and 59.03% for male's findings). However, the average normalised gain <g> has been considered as an appropriate quantitative benchmark to evaluate the peer activity effectiveness [28,29], since 1998 [30]. Taking into account the fact that the maximum normalised value achievable in our tests is 10, it can be defined by the following mathematical relationship:…”
Section: Resultsmentioning
confidence: 99%
“…The percentage increase (Δ = <s post > -<s pre >) in the Mechanics test is equal to 32.20%, with a more pronounced effect on female's value (44.19%) than male's findings (27.60%), and even bigger in Electromagnetism, which is equal to 55.48% (49.28% for female's findings and 59.03% for male's findings). However, the average normalised gain <g> has been considered as an appropriate quantitative benchmark to evaluate the peer activity effectiveness [28,29], since 1998 [30]. Taking into account the fact that the maximum normalised value achievable in our tests is 10, it can be defined by the following mathematical relationship:…”
Section: Resultsmentioning
confidence: 99%
“…Üce (2000) demonstrated by means of an achievement test consisting of multiple choice questions that the use of a conceptual change strategy in teaching the mole concept to first year general chemistry students was more effective in promoting understanding, compared to the traditional method. In a similar vein, Suppapittayaporn et al (2010), using Hake's normalised gain scores, found that the effectiveness of the traditional instruction was low, while the effectiveness of a conceptual change theoretical framework was medium, and therefore more effective.…”
Section: Literature Reviewmentioning
confidence: 92%
“…Several studies have been conducted to identify alternative conceptions for mechanical waves and wave pulses (Şengören, Tanel & Kavcar, 2006;Tongchai, Sharma, Johnston, Arayathanitkul & Soankwan, 2009). As a result, different instructional methods focusing on conceptual change have been used to identify and reduce alternative conceptions (Çalik, 2008;Suppapittayaporn, Emarat & Arayathanitkul, 2010). The authors did not find any studies reporting on instructional methods to aleviate alternative conceptions dealing specifically with interference and diffraction of waves.…”
Section: Literature Reviewmentioning
confidence: 92%
“…Suppapittayaporn et al [119] recorremà Teoria da Mudança Conceitual de Posner [120] para afirmar que o PIé uma metodologia que facilita o processo de mudança conceitual. A obtenção do feedback da aprendizagem dos estudantes, através do uso dos Testes Conceituais, foi indicada como importante frenteà Teoria das Hierarquias de Aprendizagem de Gagné [121] no estudo de Jones et al [49].…”
Section: Referencial Teóricounclassified